Pelaksanaan Pembelajaran Shalat Fardhu melalui Praktik Terbimbing bagi Anak Usia Dini - Evi Hikmiati; Hafieddh Hasan; Mahmudah Mahmudah; Syifa Fauziah (STAI Publisistik Thawalib Jakarta, 2024)
This study aims to evaluate the implementation of the guided practice method in improving prayer learning skills in Group B of RA Salafiyah Pamulian Warungpring, Pemalang in 2022, and to assess the effectiveness of the method in enhancing prayer skills. The research used a qualitative approach. The subjects were 14 students of Group B Raudatul Athfal Muslimat Salafiyah Pamulian Warungpring. Data analysis was conducted using a descriptive qualitative approach. Data collection techniques included observation, interviews, and documentation. The results showed that the implementation of the guided practice method in teaching the procedure of fardhu prayers at RA Muslimat Salafiyah Pamulian was successful. Both teachers and students accepted the achievements according to the lesson plan (RPP) in using the practice method. The results of this method also influenced the students' lifestyle by increasing their awareness of the importance of fardhu prayers and their responsibility in the afterlife. Variation in learning plays a significant role in improving students' achievements in all aspects of learning, including language, cognitive, affective, and psychomotor skills. These findings are expected to be beneficial and serve as a basis for relevant parties to enhance the religious and moral values of children.